The Role of Family Problems in the performance of the Work of Employees in Government Institutions (Raparin Journal of Humanities (RJH), 2019)
In the Kurdistan the work in government sector is a main source of work, but people believed that their work do not be done with the large number of employees, therefore a family problem might be a one of causes that impact on employee work performance.The problem of the study attempt to answer a question has family problems impact on this family member who working in governmental institutions? As a researchers observed it is be a cause to lock of employees working, in the theoretical dimension this study is important, it is be a one of a valuable source for future study and in a practical dimension is important for assessment an effect of family problems on the performance of the work of the employees, so the benefiter of the study is manager, employer, and researchers and the aim of the study is to highlight of quantity of family problems roles on employee work implementation in government institutions.For fulfillment aim of a study collect of data in working field by Descriptive approach, the sample of the study is government employee. After the questionnaire is distributed on the samples, then SPSS package is used to analyze the data that is gained from the results that the family problems had effect on employee work implantation by variables (Gender, Age, Marital status, Education and administrative positions).